Professional ethics and teacher education - Caetano, Ana (2018)
This article focuses on issues related to ethics and training, part of a research project on ethical and deontological thinking in which, during its early stages, thirty six teachers from a variety of teaching levels were interviewed. We have identified some aspects related to the ethical training of teachers which are connected to other dimensions under study, namely the regulation and creation of a deontological code and the ethical, personal and professional conceptions of teachers. In addition to an interpretative analysis of data and a brief review of current legislation and studies, we have reflected on the perspectives and strategies to be considered in the ethical training of teachers.